AKSIOLOGI BUDAYA LOKAL JAWA-BALI PADA PROSES KREATIF BERKARYA PELUKIS BALI DI YOGYAKARTA - Sucitra, I Gede Arya; Maharani, Septiana Dwiputri (Studi Budaya Nusantara, 2019)
ABSTRACT Every human being has aspects of life which include philosophy, belief, science, and art. These four aspects interact and complement each other into one whole system. This research seeks to investigate deeper about the axiological aspects of the acculturation of local cultural values in the interaction of the environment of society (culture) of different ethnic, racial, religious, and local genius values which have a shared awareness of mutual respect, tolerance and